Materials Graph Library (MatGL), an open-source graph deep learning library for materials science and chemistry - Tsz Wai Ko; Bowen Deng; Marcel Nassar; Luis Barroso-Luque; Runze Liu; Ji Qi; Atul C. Thakur; Adesh Rohan Mishra; Elliott Liu; Gerbrand Ceder; Santiago Miret; Shyue Ping Ong (npj Computational Materials)
Abstract Graph deep learning models, which incorporate a natural inductive bias for atomic structures, are of immense interest in materials science and chemistry. Here, we introduce the Materials Graph Library (MatGL), an open-source graph deep learning library for materials science and chemistry. Built on top of the popular Deep Graph Library (DGL) and Python Materials Genomics (Pymatgen) packages, MatGL is designed to be an extensible “batteries-included” library for developing advanced model architectures for materials property predictions and interatomic potentials. At present, MatGL has efficient implementations for both invariant and equivariant graph deep learning models, including the Materials 3-body Graph Network (M3GNet), MatErials Graph Network (MEGNet), Crystal Hamiltonian Graph Network (CHGNet), TensorNet and SO3Net architectures. MatGL also provides several pre-trained foundation potentials (FPs) with coverage of the entire periodic table, and property prediction models for out-of-box usage, benchmarking and fine-tuning. Finally, MatGL integrates with PyTorch Lightning to enable efficient model training.